2017
DOI: 10.1007/s10930-017-9707-0
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of C-phycocyanin Containing Protein Extract (C-PC Extract) on Human Matrix Metalloproteinases (MMP-2 and MMP-9) in Hepatocellular Cancer Cell Line (HepG2)

Abstract: Spirulina platensis :have been studied for several biological activities. In the current study C-phycocyanin containing protein extract (C-PC extract) of Spirulina platensis have been studied for its effect on human matrix metalloproteinases (MMP-1, MMP-2 and MMP-9) and tissue inhibitors of MMPs (TIMP-1 and TIMP-2). In the present study, breast cancer cell line (MDA-MB 231) and hepatocellular cancer cell line (HepG2) were examined for inhibition of MMPs at different levels of expression after C-PC extract trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Phycocyanin can inhibit the expression of COX-2 and prostaglandin E2 (PGE2), and down-regulate the MMP-9 expression by mitogen-activated protein kinase (MAPK) signaling pathway 6 . C-phycocyanin from Spirulina platensis could inhibit MMP-2 and MMP-9 expression and TIMP-2 at a mRNA expression level; however, C-phycocyanin could not have any effect on MMP-1 expressed in MDA-MB231 and TIMP-1 expressed in HepG2 cells 78 . In addition, C-phycocyanin could bind to VEGFR1 alone, and down-regulated levels of VEGF-A, MMP-2 and MMP-9 79 .…”
Section: Phycocyanin: General Propertiesmentioning
confidence: 84%
“…Phycocyanin can inhibit the expression of COX-2 and prostaglandin E2 (PGE2), and down-regulate the MMP-9 expression by mitogen-activated protein kinase (MAPK) signaling pathway 6 . C-phycocyanin from Spirulina platensis could inhibit MMP-2 and MMP-9 expression and TIMP-2 at a mRNA expression level; however, C-phycocyanin could not have any effect on MMP-1 expressed in MDA-MB231 and TIMP-1 expressed in HepG2 cells 78 . In addition, C-phycocyanin could bind to VEGFR1 alone, and down-regulated levels of VEGF-A, MMP-2 and MMP-9 79 .…”
Section: Phycocyanin: General Propertiesmentioning
confidence: 84%
“…Hence, MMPs are considered as a therapeutic target in many diseases 26. And it was reported that C-PC selectively inhibited MMPs (MMP-2 and MMP-9) in HepG2 cells 31. We found the MMP-2 protein expression in the C-PC/CMC NPs and C-PC/CMC-CD59sp NPs treatment group were significantly decreased, and MMP-2 protein expression level change in the C-PC/CMC-CD59sp NPs treatment group was more significant than CMC/C-PC NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Also, cell migration ( Figure 2I ) and invasion ( Figure 2J ) by transwell assay were reduced after transfection of si-circDHTKD1 compared to si-NC transfection. MMPs can reflect cell invasion and aggressiveness in many tumors ( 21 , 22 ). Our western blot indicated the inhibitory effects of si-circDHTKD1 on MMP2 and MMP9 protein levels compared with the si-NC group ( Figure 2K and L ), indicating that circDHTKD1 downregulation blocked cell invasion.…”
Section: Resultsmentioning
confidence: 99%